1994
DOI: 10.1037/0882-7974.9.2.303
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of adult age differences on the Raven's Advanced Progressive Matrices Test.

Abstract: The purpose of this project was to examine the nature of performance, and specifically, age-related performance, on the Raven's Advanced Progressive Matrices (APM) Test (Raven, Court, & Raven, 1983). In the 1st of 2 studies, 2 tests presumed to measure each of 4 hypothesized components of the APM and 3 tests presumed to measure processing speed were presented to 165 young adults. On the basis of correlational and confirmatory analyses, 1 of the components was not included in Study 2. The 2nd study was designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
1
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 40 publications
2
46
1
1
Order By: Relevance
“…The task for the examinee is to use abstract reasoning to identify the pattern that provides the best completion of the missing cell. A recent study involving 221 adults between 20 and 80 years of age (Salthouse, 1993a) found that 32.2% of the variance in the Raven's score was associated with chronological age, and in a similar study (Babcock, 1994) 21.2% of the variance in the Raven's score was found to be related to age.There is clearly substantial scatter in the data of Figure 1, and the proportions of variance associated with age are always substantially less than 1.0. Because many researchers may not be comfortable thinking in terms of proportions of variance, it is reasonable to question the magnitude of the age-related effects in Type A or fluid measures ofcognitive functioning.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…The task for the examinee is to use abstract reasoning to identify the pattern that provides the best completion of the missing cell. A recent study involving 221 adults between 20 and 80 years of age (Salthouse, 1993a) found that 32.2% of the variance in the Raven's score was associated with chronological age, and in a similar study (Babcock, 1994) 21.2% of the variance in the Raven's score was found to be related to age.There is clearly substantial scatter in the data of Figure 1, and the proportions of variance associated with age are always substantially less than 1.0. Because many researchers may not be comfortable thinking in terms of proportions of variance, it is reasonable to question the magnitude of the age-related effects in Type A or fluid measures ofcognitive functioning.…”
mentioning
confidence: 79%
“…The task for the examinee is to use abstract reasoning to identify the pattern that provides the best completion of the missing cell. A recent study involving 221 adults between 20 and 80 years of age (Salthouse, 1993a) found that 32.2% of the variance in the Raven's score was associated with chronological age, and in a similar study (Babcock, 1994) 21.2% of the variance in the Raven's score was found to be related to age.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Importantly, Conway et al found that the simple PS tasks did not load on the Gf factor. In other studies (e.g., Ackerman et al, 2002;Babcock, 1994), complex PS tasks are found to correlate much more strongly with intelligence and WM than do simple PS tasks. Simply put, PS tasks correlate with intelligence to the extent that they tap attentional ability (Stankov & Roberts, 1997;Wilhelm & Schulze, 2002).…”
Section: Alternative Explanationsmentioning
confidence: 99%
“…It was designed to examine the extent to which individuals can think clearly and make sense of complex information (known as "eductive" ability), and the ability to remember and reproduce information previously presented information (i.e., reproductive ability; Babcock, 1994;Raven, 2000). A large body of work has found this instrument to possess a high degree of reliability and validity among younger and older adults (Bors & Stokes, 1998;Babcock, 1994), and it has been employed with older adult populations (Basak, Boot, Voss, & Kramer, 2008). Each item is made up of a series of diagrams that follow a logical pattern; the diagram that would be in the final cell, however, is missing.…”
Section: The Trail Making Test (Tmt)mentioning
confidence: 99%